Implementasi Kebijakan Bantuan Langsung Tunai Dana Desa di Desa Taba Air Pauh Kabupaten Kepahiang - Heru Purnawan; Deni Triyanto; Subhan Ilham Thareq (Universitas Medan Area, 2022)
This BLT-DD policy was made by Taba Air Pauh Village based on a village meeting organized by the village government, the Village Consultative Body, and several village community leaders taking into account the pandemic conditions which impacted the decline in village community income. The purpose of this study is to describe the process of implementing the BLT-DD Policy as an economic solution for the Taba Air Pauh village community in the post-Covid-19 pandemic and explain what strategies are taken by the Taba Air Pauh Village Government in the process of implementing the Village Fund Direct Cash Assistance Policy (BLT). -DD) Taba Air Pauh, Tebat Karai District, Kepahiang Regency. The research method used is qualitative with a descriptive approach. The results of this study include 1. The BLT-DD policy is fully supported by all levels of government; 2. BLT-DD is direct cash assistance from the Village Fund sourced from the State Revenue and Expenditure Budget (APBN); 3. BLT-DD recipients are non-beneficiaries of Social Service assistance, Micro, middle-class Enterprises, and other assistance that are not from BLT-DD; 4. There are still BLT-DD recipients who are not yet on target; and 5. There was a crowd of villagers receiving BLT-DD at the Kepahiang branch of the National Bank of Indonesia (BNI).